Does Environmental Knowledge Matter? Social Influence and Pro-Environmental Behavior in University Students: An Indirect Effect Model - Simiyu, Gabriel; Kariuki, Valentine; Ombaba, Mwengei; Otuya, Robert (SEISENSE Journal of Management, 2022)
Purpose- This study aims to provide an analytical framework that focuses on environmental knowledge as a mechanism through which social influence enhances pro-environmental behavior among university students. Design/Methodology- The research employed quantitative strategy, cross-sectional survey design, and systematic random sampling techniques to obtain data from a sample of 335 university students using a structured self-administered questionnaire. The study hypotheses were tested using Hayes Process Macro vs. 3.5 (Model 4). Findings- Results indicate that social influence strongly impacts students’ environmental knowledge, and both variables significantly predict pro-environmental behavior. Environmental knowledge was discovered to be the strongest predictor of pro-environmental behavior among students. Finally, results show that environmental knowledge mediates the relationship between social influence and pro-environmental behavior, revealing a complimentary mediation model superior to the direct effect model. Originality- These findings reveal that social influence and students’ environmental knowledge have a strong influence in cultivating students’ pro-environmental behavior. Furthermore, the complementary mediation model, which shows superior results than the direct effect model, contributes to the body of knowledge and offers new insights into theory and practice. Practical Implications- Environmental sustainability may be positioned as a social trend by government and business agencies, such as a promotional campaign, workshops, and training to demonstrate and raise awareness about environmental issues.